Distinct difference in tumor-infiltrating immune cells between Wilms' tumor gene 1 peptide vaccine and anti-programmed cell death-1 antibody therapies. Issue 1 (29th June 2021) - Yokota, Chisato; Nakata, Jun; Takano, Koji; Nakajima, Hiroko; Hayashibara, Hiromu; Minagawa, Hikaru; Chiba, Yasuyoshi; Hirayama, Ryuichi; Kijima, Noriyuki; Kinoshita, Manabu; Hashii, Yoshiko; Tsuboi, Akihiro; et al.
Abstract: Background: Wilms' tumor gene 1 (WT1) peptide vaccine and anti-programmed cell death-1 (anti-PD-1) antibody are expected as immunotherapies to improve the clinical outcome of glioblastoma. The aims of this study were to clarify how each immunotherapy affects tumor-infiltrating immune cells (TIIs) and to determine whether the combination of these two therapies could synergistically work. Methods: Mice were transplanted with WT1 and programmed cell death-ligand 1 doubly expressing glioblastoma cells into brain followed by treatment with WT1 peptide vaccine, anti-PD-1 antibody, or the combination of the two, and survival of each therapy was compared. CD45 + cells were positively selected as TIIs from the brains with tumors, and TIIs were compared between WT1 peptide vaccine and anti-PD-1 antibody therapies. Results: Most mice seemed to be cured by the combination therapy with WT1 peptide vaccine and anti-PD-1 antibody, which was much better survival than each monotherapy. A large number of CD4 + T cells, CD8 + T cells, and NK cells including WT1-specific CD8 + and CD4 + T cells infiltrated into the glioblastoma in WT1 peptide vaccine-treated mice. On the other hand, the number of TIIs did not increase, but instead PD-1 molecule expression was decreased on the majority of the tumor-infiltrating CD8 + T cells in the anti-PD-1 antibody-treated mice. Conclusion: Our results clearly demonstrated that WT1 peptide vaccine and anti-PD-1 antibody therapies worked in the different steps of cancer-immunity cycle and that the combination of the two therapies could work synergistically against glioblastoma.